Validation of ACB in vitro and in vivo as a biomagnetic method for measuring stomach contraction - Americo, Madileine Francely [UNESP]; Marques, Rozemeire Garcia [UNESP]; Zandona, E. A. [UNESP]; Andreis, Uilian de [UNESP]; Stelzer, Marcelo [UNESP]; Cora, Luciana Aparecida; Oliveira, Ricardo Brandt de; Miranda, José Ricardo de Arruda [UNESP] (Wiley-Blackwell Publishing, Inc, 2010)
Background The aim of this study was to validate a biomagnetic method (alternate current biosusceptometry, ACB) for monitoring gastric wall contractions in rats. Methods In vitro data were obtained to establish the relationship between ACB and the strain-gauge (SG) signal amplitude. In vivo experiments were performed in pentobarbital-anesthetized rats with SG and magnetic markers previously implanted under the gastric serosa or after ingestion of magnetic material. Gastric motility was quantified from the tracing amplitudes and frequency profiles obtained by Fast Fourier Transform. Key Results The correlation between in vitro signal amplitudes was strong (R = 0.989). The temporal cross-correlation coefficient between the ACB and SG signal amplitude was higher (P < 0.0001) in the postprandial (88.3 +/- 9.1 V) than in the fasting state (31.0 +/- 16.9 V). Irregular signal profiles, low contraction amplitudes, and smaller signal-to-noise ratios explained the poor correlation between techniques for fasting-state recordings. When a magnetic material was ingested, there was also strong correlation in the frequency and signal amplitude and a small phase-difference between the techniques. The contraction frequencies using ACB were 0.068 +/- 0.007 Hz (postprandial) and 0.058 +/- 0.007 Hz (fasting) (P < 0.002) and those using SG were 0.066 +/- 0.006 Hz (postprandial) and 0.059 +/- 0.008 Hz (fasting) (P < 0.005). Conclusions & Inferences In summary, ACB is reliable for monitoring gastric wall contractions using both implanted and ingested magnetic materials, and may serve as an accurate and sensitive technique for gastrointestinal motility studies.
Keywords: Digestive physiology; Food; Gastrointestinal motility; Investigative techniques; Rats; Transducers